Do they need us? Linking functional indispensability and voice behavior: The role of psychological ownership, job insecurity and organizational ambidexterity - Alves, D.; Duarte, A. P.; Rosa, M.; Silva, S. da. (Economic and Industrial Democracy, 2024)
This study looked into how workers’ perception of their team’s functional indispensability motivates them to engage in promotive voice behavior. The mediating role of psychological ownership and the moderator roles of job insecurity and organizational ambidexterity were also examined. Data from 820 Portuguese workers from different business sectors were analyzed using multiple regression techniques. Results indicate that perceived functional indispensability is positively associated with employee voice behavior, and this relationship is mediated by increased psychological ownership of the organization. Moreover, quantitative job insecurity weakens the link between indispensability and ownership, while ambidexterity reinforces the relationship between indispensability and voice.